Synthesis of a natural product-like compound collection through oxidative cleavage and cyclization of linear peptides - Petersen, Rico (2015)
Massive efforts in molecular library synthesis have strived for the development of synthesis methodology which systematically delivers natural product-like compounds of high spatial complexity. Herein, we present a conceptually simple approach that builds on the power of solid-phase peptide synthesis to assemble precursor peptides (oligomers) designed to undergo oxidative cascade reactions. By harnessing the structural side-chain diversity and inherent stereochemical features offered by readily available amino acids (monomers), a proof-of-concept collection of 54 skeletally and stereochemically diverse compounds was generated, and selected compounds were elaborated into isoform-selective metalloprotease inhibitors.